Subclinical Thyroid Dysfunction was not Associated with Cardiac Arrhythmias in a Cross-Sectional Analysis of the ELSA-Brasil Study - Kamilla Maria Araújo Brandão Rajão (Arquivos Brasileiros de Cardiologia, 2019)
Abstract Background: The association of subclinical thyroid dysfunction (STD) with cardiac arrhythmias remains controversial, particularly in the non-elderly population. Objective: To investigate whether STD was associated with cardiac arrhythmias in a cohort of middle-aged and older adults. Methods: Baseline data of the Longitudinal Study of Adult Health, ELSA-Brasil (35-74 years) were collected from 2008 to 2010. After exclusion of clinical hypothyroidism and hyperthyroidism, participants were categorized as euthyroidism (TSH = 0.4-4.0 µU/mL), subclinical hypothyroidism (TSH > 4.0 µU/mL; FT4 = 0.8-1.9 ng/dL), and subclinical hyperthyroidism (TSH < 0.4 µU/mL; FT4 = 0.8-1.9 ng/dL). The prevalence rates of tachycardia (HR > 100) and bradycardia (HR < 60), atrial fibrillation/flutter, conduction disorders, extrasystoles, low QRS voltage, prolonged QT intervals, and persistent supraventricular rhythms were compared between groups after adjusting for age, sex, comorbidities, lifestyle, body mass index and medications. Results: The HR data of 13,341 participants (52% female; median age, 51 years) and the electrocardiogram readings of 11,795 were analyzed; 698 participants (5.23%) were classified as subclinical hypothyroidism, 193 (1.45%) as subclinical hyperthyroidism, and 12,450 (93.32%) as euthyroidism. The prevalence of rhythm and conduction disorders was similar, as were HR medians, even in the subgroups with TSH < 0.01 UI/mL or > 10.0 UI/mL or in older adults. Conduction disorders were less prevalent in older adults with subclinical hypothyroidism (adjusted OR = 0.44; 95% CI 0.24 to 0.80). Conclusion: In this large, multicenter and cross-sectional study, STD was not associated with cardiac arrhythmias, but a longitudinal assessment is necessary.